HUBUNGAN ANTARA UMUR DAN PARITAS DENGAN KEJADIAN PLASENTA PREVIA PADA IBU BERSALIN DI RSUD ARJAWINANGUN KABUPATEN CIREBON TAHUN 2022 - Laily Rachmawati; Annesya Atma Battya (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
Cases of bleeding as the main cause of maternal death can occur dering pregnancy, childbirth and the puerperium. Predisposisi factor for placenta previa were ade over 25 years, multipara, history of curettage and smoking at parkland hostiter the prevalence of placenta previa was 0,5%. This study aims to determine the relationship between age and parity with the incidenceof placenta previa in mothers giving birth at Arjawinangun Hospital regency Cirebon in 2022. The research method used analytic survey. The research design used cross sectional. This study used an observation approach or collection from medical records of patients with placenta previa using total sampling technique. The result of this study were that there was a relationship between age and parity with the incidence of placenta in mothers giving birt at Arjawinangun hospital with a pvalue of 0,006 < 0,05 on the age variable and a pvalue of 0,000 < 0,05 on the paritas variable.